The effect of pro-/synbiotic supplementation on the brain-derived neurotrophic factor: a systematic review and meta-analysis of randomized controlled trials. Issue 17 (9th August 2022) - Foshati, Sahar; Akhlaghi, Masoumeh; Babajafari, Siavash
Abstract : We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to investigate the impact of pro-/synbiotic supplementation on brain-derived neurotrophic factor (BDNF) levels. Abstract : There is growing interest in supplementation with pro-/synbiotics for brain and mental health. Animal studies have reported that pro-/synbiotic administration can increase the brain-derived neurotrophic factor (BDNF), a key regulator of neuronal function. Nevertheless, the results obtained from human studies are inconsistent and conflicting. Therefore, we aimed to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) to investigate the impact of pro-/synbiotic supplementation on BDNF levels. Scopus, Medline, Web of Science, Cochrane Library, and Google Scholar were searched up to July 10, 2022 to find eligible RCTs. The weighted mean difference (WMD) and 95% confidence interval (CI) were computed for BDNF using a random-effects model. In the present study, 10 RCTs with 12 treatment arms consisting of 652 participants were included. The meta-analysis revealed that supplementation with pro-/synbiotics significantly increased BDNF concentrations in comparison with the placebo (WMD: 0.20 ng mL −1, 95% CI: 0.06 to 0.34, I 2 = 86.6%). Moreover, subgroup analysis showed that the target population, ethnicity and the mean age of participants, the number and type of probiotic strains, administration form, and the dose and duration of pro-/synbiotic supplementation were the potential sources of heterogeneity between RCTs. In conclusion, pro-/synbiotic administration can be considered as a BDNF enhancer and a possible brain booster.